STUDENTS’ EAGERNESS TO HAVE ONLINE CLASSES ON ZOOM APP - Hesthi Herusatoto; Sri Endah Setia Rini (Conscientia, 2021)
Covid 19 has changed many things, including the world of education. Lessons commonly provided face-to-face had to be given online using conference apps. This research was intended to find out if students of STBA LIA Yogyakarta showed eagerness to participate in online Zoom classes. Data were collected by distributing a survey of which the results were analyzed descriptively using cross tabulation between questions in the survey. The results indicate that 30% of students were eager to attend online classes using Zoom. The eagerness was shown by their participation in online lectures. Conversely, those who were less eager mainly have such problems as network, internet data, and personal problems.